SAFH Identify - BONFIM, Edicleia Veras; BRITO, José Lucas Soares de; CUNHA, Rafaela Rivera de Freitas; LANDIN, Rayan Barco Paes; GARCIA, Thayná Santos (172, 2014)
Nosso mundo é cenário de guerras, mas não só as que ficam famosas na história, mas sim a diária, que se vivencia na vida, em todas as manhãs, no trabalho, no lazer, e esse trabalho trás a proposta para resolução parcial desse problema, sendo o SAFH Identify o dispositivo responsável por tal feito.

Our world is a scene of wars, but not only those that are famous in history, but rather the daily one, which is experienced in life, every morning, at work, in leisure, and this work brings the proposal for a partial resolution of this problem, SAFH Identify being the device responsible for this.
Keywords: Softwares; Hardware; Informação e Comunicação